Ethanol acquisition from Sechium edule soluble solid, using Saccharomyces cerevisiae for fermentation (Revista de Investigaciones Universidad del Quindío, 2011)
Biofuels, like ethanol, have now become an alternative for power generation more environmentally friendly, but his production has shown a number of shortcomings within which are the use of raw materials and food corn and sugarcane, it is therefore necessary to seek alternatives for its production Chayote (citron) is a fruit that has good content of sugar, starch and cellulose, is found in the coffee region and is not considered a staple. For the above in this paper was intended to generate bioethanol based on soluble solids, using Saccharomyces cerevisiae as a leavening agent.  The ethanol yield obtained was 52.18 ml/100g of ss and was determined by infrareds pectroscopy.
Keywords: Soluble solids; bioethanol; Sechium edule